The Effectiveness of Using Guessing Game to Improve English Writing Skill - Cut Putro Humaira; Iskandar Abdul Samad; Samsul Bahri Ys (Research in English and Education Journal, 2022)
Writing is a crucial skill to have while learning English. Students must be able to write in English. Students at SMPN 10 Banda Aceh still have poor writing skills. Students continue to struggle with writing, particularly descriptive text. This is due to a lack of enthusiasm as well as monotonous classes. As a result, researcher was interested in using guessing games to help students improve their writing skills on descriptive text. The purpose of this study is to see if guessing games could help 7th grade students at SMPN 10 Banda Aceh improve their ability to write descriptive text. This research takes a quantitative approach and uses a pre-experimental design with a one-group pre-test post-test design. The sample for this study was 28 students from a total population of 89 students. The data was gathered by pre-tests and post-test. From the pre-test to the post-test, the findings of this study indicated a significant increase. This is seen by the increase in the average score from 37.23 to 68.21, as well as the improvement in each indicator by an average of 79 percent. It is clear that Ha has been accepted and Ho has been rejected. As a result, guessing games are effective in improving students’ descriptive text writing skills.